2000
DOI: 10.1046/j.1469-7580.2000.19610055.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial glycoconjugates: a comparative lectin study of the brain, retina and myocardium

Abstract: There is evidence that the endothelial cell (EC) glycocalyx is a significant determinant of vascular permeability, acting as a charge-size filter to permeant molecules. We have therefore examined its oligosaccharide composition in 3 classes of microvessel with differing permeabilities. EC in rat brain, retina and myocardium were labelled with a panel of lectins and subjected to a semiquantitative analysis. Surprisingly, no substantial differences were evident for any lectin labelling between the 3 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Wheat germ agglutinin (WGA) also labeled numerous N-acetyl-glucosamines and Nacetyl-neuraminic acids present on the endothelium, but α-fucose was not detected in the brain. These findings were also confirmed by another study [154]. Not only healthy cells, but also malignant cells exhibit a special pattern of sugar moieties on their surface, making lectins good candidates for the targeting of drugs.…”
Section: Coating With Lectinssupporting
confidence: 77%
“…Wheat germ agglutinin (WGA) also labeled numerous N-acetyl-glucosamines and Nacetyl-neuraminic acids present on the endothelium, but α-fucose was not detected in the brain. These findings were also confirmed by another study [154]. Not only healthy cells, but also malignant cells exhibit a special pattern of sugar moieties on their surface, making lectins good candidates for the targeting of drugs.…”
Section: Coating With Lectinssupporting
confidence: 77%
“…The connective tissue was least labelled by SNA-I recognizing sialic acid in the α 2-6 glycosidic linkage (Lawrenson et al 2000). However, MAA that labels sialic acid in α 2-3 linkage to β-galactose stained connective tissue and basement membranes of muscle fibres intensely.…”
Section: Discussionmentioning
confidence: 99%
“…Although not specifically studied, retinal endothelial cells are likely to assist mural myocytes and pericytes in sensing and transducing mechanical forces. The retinal endothelium is coated with a glycocalyx (Lawrenson et al, 2000), which has been shown to function as a mechanical sensor and transducer in extra-ocular endothelia (Tarbell and Ebong, 2008). Retinal vascular endothelium also has the ability to detect chemical perturbations, including hypoxia and hypercapnia, and the metabolite, lactose (Pournaras et al, 2008).…”
Section: Anatomical and Physiological Considerationsmentioning
confidence: 99%